The Effect of Student’s Gender and presence on Academic Performance in Amhara Region with special reference to University of Gondar, Ethiopia - Nachimuthu, Dr.Kavitha; Awoke Kassa, Mr.Wondim (International Journal of Scientific Research and Management (IJSRM), 2018)
Quality education is the crucial for over development of the country. But there are different challenges for student to get quality education which led for poor academic performance.  The study was conducted in the University of Gondar, Ethiopia to examine determinants of academic performance of the student. It was conducted at the second semester results of the final score in three courses for the academic year 2016/17 (Farming System Research and Innovation, Innovation System and Agricultural and Rural Extension). The courses were delivered for second year rural development and agricultural extension, adult education and community development 2nd year and animal production and extension 3rd year in the University of Gondar. Totally 118 students considered and stratified as male and female to compare and contrast the academic performance based on their attendance and total score. The multiple regressions was used to carried out to determine the impact of students’ attendance and gender (being male and female) at teaching and learning process in their final academic performance. The study reveals that female students attained more than male student but on average they perform less than male students. Both gender and attendance have significant effect on academic performance of the student. Gender was significant at 1% probability and attendance was significant at 1%.  Therefore, university should give emphasis for these determinants and further study should be conducted to identify other factors which hinder academic performance of the student.